Human rights activism and the end of the Cold War : a transnational history of the Helsinki network - Snyder, Sarah B., 1977- (New York, NY : Cambridge University Press, 2013)
This work explores how, in the aftermath of the signing of the Helsinki Final Act in 1975, a transnational network of activists committed to human rights in the Soviet Union and Eastern Europe made human rights a central element of East-West diplomacy.
1. Bridging the East-West divide : the Helsinki Final Act negotiations -- 2. "A sort of lifeline" : the Helsinki Commission -- 3. Even in a Yakutian village : Helsinki monitoring in Moscow and beyond -- 4. Follow-up at Belgrade : the United States transforms the Helsinki process -- 5. Helsinki watch, the IHF, and the transnational campaign for human rights in Eastern Europe -- 6. Human rights in East-West diplomacy -- "A debate in the fox den about raising chickens" : the Moscow conference proposal -- 8. 'Perhaps without you, our revolution would not be."
"First published 2011. First paperback edition 2013"--Title page verso
Includes bibliographical references and index.
Keywords: Conference on Security and Cooperation in Europe (Organization); Conference on Security and Cooperation in Europe (Organization); Final Act (Conference on Security and Cooperation in Europe); Human rights; Human rights -- Europe, Eastern; Human rights -- Soviet Union; Human rights advocacy; Cold War; Human rights; Human rights advocacy; Europe, Eastern; Soviet Union